Indonesian Language Training on the Use of Standard Spelling for Writing at MTs Al-Kautsar Bayuning. - ifah hanifah (Jurnal Pengabdian Pemersatu Bangsa, 2026)
aims to improve students' understanding and application of spelling in accordance with the General Guidelines for Indonesian Spelling (PUEBI) among students of Al-Kautsar Islamic Boarding School, Bayuning. The method used is a workshop involving 16 students from grades VII and VIII. The workshop consists of material delivery, question and answer sessions, as well as pre- and post-training evaluations. The evaluation results show that 62.5% of participants experienced improvement in the use of capital letters, word writing, and punctuation. However, 37.5% of participants have not shown significant progress. These results indicate that spelling training has a positive impact on students' writing literacy skills but also emphasize the need for follow-up in the form of continuous training. This activity can serve as an initial model for strengthening written language skills in Islamic boarding school environments, as well as encouraging the correct and proper application of spelling in daily practice.